TEACHING CLINICAL REASONING TO PHYSIOTHERAPISTS IN SAUDI ARABIA: A THEORETICAL REPORT (International Journal of Physiotherapy, 2017)
Background: Clinical reasoning (CR) is an essential skill that should be taught to all healthcare professionals. In physiotherapy, it is a cognitive process whereby physiotherapists collect and assess patient data to make a diagnosis and develop an effective treatment plan. Several teaching and learning theories have been developed and used in healthcare education. The purpose of teaching is to facilitate the learning process and the successful development of practitioners in the community. Learning is defined as a knowledge process that is developed through experience which is used to manage daily life situations. The aim of this report is to explore teaching and learning theories and strategies to teach clinical reasoning to physiotherapy students in Saudi Arabia.Discussion: Although it is challenging to completely change the teaching methods in Saudi universities due to the education system rules already in place, some modules in physiotherapy are different, as they are practical and based mainly in a clinical hospital setting. As such, certain teaching and learning theories could be employed to facilitate student teaching. Indeed, a mixed method based on several theories taking into consideration the context, culture, students’ learning styles and the type of knowledge would be most appropriate.Conclusion: There is a debate about the best theory for teaching physiotherapy students. In the context of clinical reasoning, a behaviorism approach is not suitable, in contrast, constructivism is more appropriate, and thus, Saudi physiotherapy educators should consider constructivism strategies for teaching clinical reasoning.